"Time is a Great Teacher, but Unfortunately It Kills All Its Pupils": Insights from Psychiatric Service User Engagement. Issue 4 (18th November 2021) - Soklaridis, Sophie; Cooper, Rachel Beth; de Bie, Alise
Abstract: In this Foundations article, the authors reflect on the meaning of time through their past work creating novel roles for psychiatric service users to be involved in the education of health professions trainees and faculty. Inspired by music composer Hector Berlioz, the authors explore and critique the ableist, chrononormative temporalities of academia, and medical education. The authors introduce the conception of crip time from critical disability studies and use it to reflect on their experiences of the different temporalities that people bring to service user engagement and other collaborative projects. "Crip time" can help challenge notions of pace and productivity to create a more inclusive space for teachers and learners in health professions education.